ПРОБЛЕМЫ ФОНЕТИЧЕСКОЙ ИНТЕРФЕРЕНЦИИ ПРИ ОБУЧЕНИИ АНГЛИЙСКОМУ ЯЗЫКУ - Даўлетмуратова, Х.Е. (SCIENCE and SOCIETY, 2021)
Interference, in its general understanding, and phonetic interference have never been the subject of research regarding the Karakalpak language. This article makes the first attempt to observe and describe this phenomenon based on the pronunciation skills of English pronunciation in the Karakalpak audience. The author provides a brief excursion on the problem of types of interference in general terms; and against the background of these data, phonetic interference stands out as the subject of research in this study with examples of the pronunciation of English sounds by native speakers of the Karakalpak language.